PERANAN UNICEF DALAM MEMULIHKAN DAN MEMPERBAIKI LAYANAN AIR BERSIH DAN SANITASI DI ACEH - Asri Wulandhari (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to analyze the programs and challenges faced by UNICEF in restoring and improving clean water and sanitation services in Banda Aceh. This research is descriptive with data collection techniques in the form of documentation studies. The results showed that the UNICEF program was rehabilitation of drinking water installation maintenance, design and reconstruction of water pipelines, water supply in rural areas, rehabilitation of sewage treatment plant installations and increasing PDAM capacity. Meanwhile, the challenge faced is that Aceh is an area that has been in conflict with the central government for 30 years because of the separatist movement (GAM). However, this is not a big challenge because both parties signed a 2005 peace agreement; the ongoing process of decentralization; there is a transition to recovery towards sustainable development.